Strand 4: The Internet Express: A Case Study in On-Line Public Access and Training - Neilson, Irene; Billington, Andie; Charlton, Colin; Little, Janet (Proceedings of the International Conference on Networked Learning, 1998)
In order to ensure that the opportunity for Networked Learning is exploited by all sectors of the community, access to, and training in, the use of computers and the basic software packages on which exploitation of the power of the Internet depends need to be widely available. This paper discusses the issues which have arisen in one "public access to the Internet" programme, the Internet Express, based in public libraries in the Merseyside area of the UK. This programme focuses on providing free. Internet access and training to residents of particularly socially deprived areas of Merseyside. The programme is part of a general attempt within the region to use telematics as a tool in the process of urban regeneration.